Keadilan Ekonomi dalam Intervensi Harga Gabah oleh Bulog: Kajian Nilai Maslahah bagi Petani di Duampanua - Gustia; Syahriyah Semaun; An Ras Try Astuti; Muliati; Damirah (Universitas Muhammadiyah Surabaya, 2025)
Abstract The fluctuation of rice grain prices in Duampanua District, Pinrang Regency, reflects structural market imbalances dominated by middlemen (tengkulak). This condition creates economic injustice for farmers who are forced to sell their harvests below the Government Purchase Price (HPP). This study aims to analyze economic justice within Bulog’s price intervention policy and to assess the extent to which the policy embodies the value of maslahah (public benefit) for farmers from the perspective of Islamic economics. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with farmers, middlemen, and Bulog officials, as well as documentation of policies and relevant literature. Data analysis was carried out through reduction, presentation, and conclusion drawing based on distributive justice and maslahah principles. The results show that Bulog’s intervention through the establishment of HPP and direct purchase mechanisms has contributed to price stability; however, its effectiveness remains limited due to bureaucratic constraints, lack of socialization, and limited farmer access. From an Islamic economic perspective, Bulog’s policy reflects elements of economic justice and protection for the weak (al-mustadh‘afin), yet the value of maslahah has not been fully realized since most farmers still depend on middlemen. Therefore, strengthening Bulog’s institutional capacity and enhancing coordination with local governments are essential to achieving a fair and sustainable grain distribution system in line with Islamic economic principles. Keywords: Economic Justice, Price Intervention, Bulog, Maslahah, Rice Farmers Abstrak Fenomena ketidakstabilan harga gabah di Kecamatan Duampanua, Kabupaten Pinrang, menunjukkan adanya ketimpangan dalam struktur pasar yang didominasi oleh tengkulak. Kondisi ini menimbulkan ketidakadilan ekonomi bagi petani yang terpaksa menjual hasil panennya di bawah Harga Pembelian Pemerintah (HPP). Penelitian ini bertujuan untuk menganalisis keadilan ekonomi dalam kebijakan intervensi harga yang dilakukan oleh Perum Bulog serta menilai sejauh mana kebijakan tersebut mencerminkan nilai maslahah bagi petani dalam perspektif ekonomi Islam. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data diperoleh melalui wawancara mendalam dengan petani, tengkulak, dan pihak Bulog, serta dokumentasi kebijakan dan literatur terkait. Analisis dilakukan melalui proses reduksi data, penyajian data, dan penarikan kesimpulan berdasarkan prinsip keadilan distributif dan nilai maslahah. Hasil penelitian menunjukkan bahwa intervensi Bulog melalui penetapan HPP dan pembelian langsung telah berkontribusi terhadap stabilitas harga, namun efektivitasnya masih terbatas akibat kendala birokrasi, minimnya sosialisasi, dan keterbatasan akses petani. Dalam perspektif ekonomi Islam, kebijakan Bulog mengandung unsur keadilan ekonomi dan perlindungan terhadap pihak yang lemah (al-mustadh‘afin), namun nilai maslahah belum sepenuhnya terwujud karena sebagian besar petani masih bergantung pada tengkulak. Oleh karena itu, diperlukan penguatan kelembagaan Bulog dan sinergi dengan pemerintah daerah untuk mewujudkan sistem distribusi gabah yang berkeadilan dan berkelanjutan sesuai prinsip ekonomi syariah. Kata Kunci: Keadilan Ekonomi, Intervensi Harga, Bulog, Maslahah, Petani Gabah